2003
DOI: 10.1038/sj.gt.3302083
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel gene delivery scaffold utilizing colloidal gold–polyethylenimine conjugates for DNA condensation

Abstract: e have developed a novel gene delivery scaffold based on DNA plasmid condensation with colloidal gold/polyethylenimine conjugates. This scaffold system was designed to enable systematic study of the relationships between DNA complex physical properties and transfection efficiency. Using an enhanced green fluorescent protein-coding reporter plasmid and a Chinese hamster ovary cell line, we have measured the transfection efficiencies of our complexes using flow cytometry and their cytotoxicities using the trypan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 22 publications
1
56
0
1
Order By: Relevance
“…32 Similarly, the protective properties of the gold coating have also been reported by others. 33 However, the literature also reported conflicting data regarding the cytotoxicity of gold nanoparticles in vitro. For example, some researchers demonstrated that different sized gold nanoparticles with varying surface chemistries were not toxic to human cells.…”
Section: Effect Of Fe 3 O 4 @Au Composite Mnps On the Organsmentioning
confidence: 98%
“…32 Similarly, the protective properties of the gold coating have also been reported by others. 33 However, the literature also reported conflicting data regarding the cytotoxicity of gold nanoparticles in vitro. For example, some researchers demonstrated that different sized gold nanoparticles with varying surface chemistries were not toxic to human cells.…”
Section: Effect Of Fe 3 O 4 @Au Composite Mnps On the Organsmentioning
confidence: 98%
“…Recently, encouraging results have been obtained that demonstrate transfection efficiency of plasmid expression vectors are greatly enhanced when the pDNA is complexed to various biopolymers. [11][12][13][14] Studies are ongoing in our laboratory to test the efficacy of various biopolymer-pDNA complexes to produce higher and more consistent levels of trans-myosin expression following in vivo gene transfer.…”
Section: Future Directionsmentioning
confidence: 99%
“…The AT muscle was pulverized in liquid N 2 , and total RNA was isolated using the TRIzol reagent (Invitrogen, Carlsbad, CA, USA). Total RNA was reverse transcribed (Superscript II, Invitrogen) to cDNA using an oligo (dT) [12][13][14][15][16][17][18] primer. Full-length MLC1 f was amplified from the cDNA using a sense primer (5 0 -TTTATTGG GGCGGCCGCCTAGGCACTGGGCTGAGGAT-3 0 ) and -TTTGGTGGTACCGCCCTAAACTTT GGACAGAT-3 0 ) complimentary to part of the 5 0 UTR and 3 0 UTR, respectively (NotI and KpnI sites underlined).…”
Section: Plasmid Expression Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…GNPs are used as immunostaining marker particles for electron microscopy and as chromophores for immunoreactions and nucleic acid hybridisation [12,13]. Their application for gene delivery into cells has also been reported [14][15][16][17]. In addition, GNPs have attracted attention as photothermal agents in hyperthermia treatment [18].…”
Section: Introductionmentioning
confidence: 99%